PENGARUH BRAND AWARENESS, BRAND IMAGE, DAN BRAND LOYALTY, TERHADAP PARENT BRAND â€œTOP COFFEEâ€ DI SURABAYA DENGAN BRAND EXTENSTION SEBAGAI VARIABEL INTERVENING - SANTOSO, DAVID (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
The expansion of the brand (brand extension) is a situation where a company to use an existing brand to launch a product in a new category. Several things can affect the expansion of the brand is brand awareness, brand image, and brand loyalty. The research aims to know the influence of brand awareness, brand image, and brand loyalty, to the parent brand "top coffee" in surabaya with brand extension as intervening variable. In this study used is the conclusive research on the study of experimental or causal research. Sampling-taking techniques used are non probability sampling. The type of method used is the purposive sampling. The sample used was 200 Top Coffee consumer in Surabaya. Data were collected using a questionnaire. The technique used is the analysis of structural equation modeling with Lisrel program assistance. The results of this analysis indicate that brand awareness, brand image and brand loyalty effect directly against the brand extention, and indirectly to the parent brand using the brand extention as intervening variable. In addition, the study found that the brand extention effect on parent brand